2015
DOI: 10.4103/1450-1147.150543
|View full text |Cite
|
Sign up to set email alerts
|

The Added Value of a Single-photon Emission Computed Tomography-Computed Tomography in Sentinel Lymph Node Mapping in Patients with Breast Cancer and Malignant Melanoma

Abstract: Single-photon emission computed tomography-computed tomography (SPECT-CT) allows for physiological and anatomical co-registration in sentinel lymph node (SLN) mapping and offers additional benefits over conventional planar imaging. However, the clinical relevance when considering added costs and radiation burden of these reported benefits remains somewhat uncertain. This study aimed to evaluate the possible added value of SPECT-CT and intra-operative gamma-probe use over planar imaging alone in the South Afric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The addition of SPECT/CT in SLN mapping also eliminates false positive results. It may detect unspecific hot foci that might be incorrectly considered SLNs by PLS [23,27]. In our study, SPECT/CT excluded two false positives, one case of truncal and one case of lower limb melanoma.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The addition of SPECT/CT in SLN mapping also eliminates false positive results. It may detect unspecific hot foci that might be incorrectly considered SLNs by PLS [23,27]. In our study, SPECT/CT excluded two false positives, one case of truncal and one case of lower limb melanoma.…”
Section: Discussionmentioning
confidence: 74%
“…Despite the favorable results of SPECT/CT over conventional PLS in patients with melanoma, some authors still believe its use should not be mandatory because the two imaging modalities present similar sensitivities in most cases. Moreover, SPECT/CT is more expensive, requires extra time, and delivers an additional, yet low radiation dose [8,27,28]. It has been suggested that this method should only be used in patients with non-visualization of SLN on planar imaging, where drainage pattern is variable or unpredictable and when conventional imaging is difficult to interpret [8,29,30]; however, the introduction of improved SPECT/CT systems and advanced detection techniques have led to a higher number of identified SLNs and better surgical workflow, without increasing the overall operation time [31].…”
Section: Discussionmentioning
confidence: 99%
“…One additional record was retrieved after cross checking the references. The characteristics of the 20 studies [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ] selected for the meta-analysis were presented in Table 1 . Only 17/19 studies with a total number of 1438 patients were available for the calculation of the pooled DR of the SPECT/CT and PL.…”
Section: Resultsmentioning
confidence: 99%